World Economic Outlook, April 1988. (World Economic Outlook; World Economic Outlook ;, 1988)
The paper describes developments in the world economy during 1987-88, and discusses considerations underlying the IMF staff's short-term projections. The paper highlights that although the world economy is continuing to expand at a moderate pace, the persistence of large fiscal and external imbalances clouds the international economic outlook. An important positive development in 1987 was the strengthening of policy coordination among the major industrial countries. The paper assesses the policy issues facing the industrial countries, against the background of alternative scenarios of medium-term developments.